African traditional religion and religious education - Shorter, Aylward (African Ecclesial Review, 1972)
The subject of this article is a large one and it will be approached from several angles. Firstly, an answer must be found to the question: Why is African Traditional Religion in the Religious Education Syllabus today? Secondly, we must deal with the position and role of African Traditional Religion in a changing Africa as well as its significance in the lives of students. Then we shall deal with the problem of the dialogue between Christianity and African Traditional Religion, and finally with the presentation of African Traditional Religion in the class-room and in the Religious Education Syllabus. Although Islam is confronted by a problem similar to that of Christianity, we shall be dealing with the question from a Christian point of view only. This is chiefly because the author is not qualified to take the Muslim point of view.
Keywords: Africa – Education; Christianity and African religions; Religious education